1997
DOI: 10.1002/(sici)1096-9861(19970915)386:1<8::aid-cne3>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron number in neonatal and adult rats estimated by means of stereologic and profile-based methods

Abstract: Postnatal neuron addition, if it occurred, would have profound implications both for the conceptualization of developmental processes and for efforts directed at replacing neurons that were lost to injury or disease. Although dorsal root ganglia (DRGs) offer the advantages of clear boundaries and functional homogeneity, studies comparing neuron number in the DRGs of animals of different ages or sizes have yielded conflicting results. In the present study, neuron number in DRGs L3-L6 was compared in neonatal (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…In agreement with the results of Farel (2003), a greater number of neurons in the hypogastric ganglion of rats of 24 months than in rats of 4 months was reported by Warburton and Santer (1997) and a greater number of neurons in the dorsal root ganglia of rats of 80 days than rats of 11 days was also stated by Popken and Farel (1997). Similarly, Gagliardo et al (2005) have reported a significant 17· increase in the total number of dog's inferior mesenteric ganglion neurons during the post-natal development, i.e.…”
Section: Total Number Of Neuronssupporting
confidence: 90%
“…In agreement with the results of Farel (2003), a greater number of neurons in the hypogastric ganglion of rats of 24 months than in rats of 4 months was reported by Warburton and Santer (1997) and a greater number of neurons in the dorsal root ganglia of rats of 80 days than rats of 11 days was also stated by Popken and Farel (1997). Similarly, Gagliardo et al (2005) have reported a significant 17· increase in the total number of dog's inferior mesenteric ganglion neurons during the post-natal development, i.e.…”
Section: Total Number Of Neuronssupporting
confidence: 90%
“…However, there has been little investigation of neurogenesis and some is still controversial in DRG of PNS (Devor et al 1985;Devor and Govrin-Lippmann 1991;Farel 2002Farel , 2003Groves et al 2003;La Forte et al 1991;Namaka et al 2001;Popken and Farel 1997). We have demonstrated here, that inhibition of NO produced in DRG neurons-satellite glia (homologous to Schwann cells) co-cultures, in absence of NGF, has a direct effect on nestin + cell numbers in vitro and axotomized DRG in vivo.…”
Section: Discussionmentioning
confidence: 63%
“…Although the vast majority of neurons are differentiated before birth, there are a few special areas in the brain region, such as subventricular zone of the lateral ventricles and subgranular zone of the dentate gyrus, which generate large numbers of neurons during postnatal development (Alvarez-Buylla et al 2001;Gage 2000;Goldman and Luskin 1998;Zhu et al 2006). Postnatal neurogenesis in the peripheral nervous system (PNS) such as dorsal root ganglion (DRG) has been reported, but not as well defined as in the CNS (Devor et al 1985;Devor and Govrin-Lippmann 1991;Farel 2002Farel , 2003Groves et al 2003;La Forte et al 1991;Namaka et al 2001;Popken and Farel 1997). Postnatal neurogenesis in DRG occurs at various time points depending on the age and injury to their axons.…”
Section: Introductionmentioning
confidence: 99%
“…Because we were interested in relative differences and not necessarily an absolute value of BrdU-labeled cells in DG, BrdU positive cells in the entire DG were quantified by profile-sampling methods [47]. In the x-y plane, BrdU positive cells limited to the subgranule cell layer were manually counted in a blind fashion at 40× magnification (Olympus, BX60, Center Valley, USA).…”
Section: Methodsmentioning
confidence: 99%